Conveyor belt

JP2025024883APending Publication Date: 2025-02-21CHUKOH CHEM IND LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2023129244
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-08-08
Publication Date
2025-02-21

Smart Images

  • Figure 2025024883000001_ABST
    Figure 2025024883000001_ABST
Patent Text Reader

Abstract

To provide a conveyor belt with an anti-meandering guide that has high heat resistance and can contribute to downsizing of conveyor belt equipment.SOLUTION: Conveyor belt has a belt base material and an anti-meandering guide attached to a part of one side of the belt base material. The anti-meandering guide is attached along the running direction of the conveyor belt and comprises a porous fluoropolymer rod. The rod has a microstructure in which nodes and fibrils are arranged alternately along their length in a longitudinal cross section, with the number of node-fibril pairs per 200 μm along their length being 11 or more, and the porosity of 30-90%.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] FIELD OF THE DISCLOSURE An embodiment of the present invention relates to a conveyor belt. [Background technology]

[0002] During the manufacture of industrial products, the products are transported by a conveyor belt. In a conveyor belt device, in order to prevent the conveyor belt from meandering, a technique is known in which a groove is provided in the pulley that drives the conveyor belt, and a meandering prevention guide that fits into the groove of the pulley is attached to one side (back side) of the belt base material as the conveyor belt. When such a conveyor belt is hung over the pulley with the meandering prevention guide fitted into the groove and operated, the movement of the belt base material is restricted by the meandering prevention guide fitted into the groove of the pulley, so that meandering of the conveyor belt can be prevented.

[0003] Conventionally, materials used for anti-meandering guides include urethane rubber, silicone rubber, and fluororubber (Patent Document 1).

[0004] The meandering prevention guide made of the above-mentioned rubber material does not have sufficient heat resistance and cannot be used for heat-resistant applications. This problem can be solved by making the meandering prevention guide out of a heat-resistant material, such as polytetrafluoroethylene.

[0005] In addition, in order to reduce the size of the conveyor belt device including the pulley, it is necessary to reduce the diameter of the pulley. In this case, when the meandering prevention guide of the conveyor belt passes through the groove of the pulley, a difference in elongation occurs between the inner and outer circumferential sides of the meandering prevention guide, which causes a problem of distortion between the meandering prevention guide and the belt base material. If this problem cannot be solved, it will be difficult to reduce the diameter of the pulley and, ultimately, the size of the conveyor belt device. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] JP 2012-014201 A Summary of the Invention [Problem to be solved by the invention]

[0007] An object of the present invention is to provide a conveyor belt having a meandering prevention guide which has high heat resistance and can contribute to the miniaturization of a conveyor belt device. [Means for solving the problem]

[0008] A conveyor belt according to an embodiment includes a belt base material and a meandering prevention guide attached to a portion of one side of the belt base material. The meandering prevention guide is attached along the running direction of the conveyor belt and is made of a porous fluororesin rod. In a longitudinal cross section cut along the length, the rod has a microstructure in which nodes and fibrils are alternately arranged in the length direction, the number of node-fibril pairs per 200 μm straight line along the length direction is 11 or more, and the porosity is 30 to 90%. [Brief description of the drawings]

[0009] [Figure 1] FIG. 2 is a longitudinal cross-sectional view of the conveyor belt according to the embodiment, taken along the width direction. [Diagram 2] FIG. 2 is a perspective view showing a state in which the conveyor belt according to the embodiment is stretched around a pulley, with a portion of the conveyor belt cut away. [Diagram 3] FIG. 2 is a front view illustrating a method for measuring the minimum bending radius of a PTFE rod. [Figure 4] FIG. 2 is a perspective view illustrating a method for measuring the compressibility of a PTFE rod in the length direction and thickness direction. [Diagram 5] 1 is a scanning electron microscope photograph showing a longitudinal cross section of the PTFE rod of Example 1 cut along the length direction. [Figure 6] 4 is a scanning electron microscope photograph showing a longitudinal cross section of the PTFE rod of Comparative Example 2 cut along the length direction. [Figure 7]4 is a scanning electron microscope photograph showing a longitudinal cross section of the PTFE rod of Example 2 cut along the length direction. [Figure 8] 4 is a scanning electron microscope photograph showing a longitudinal cross section of the PTFE rod of Comparative Example 3 cut along the length direction. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] Hereinafter, the structure of a conveyor belt according to an embodiment will be described with reference to FIGS. Fig. 1 is a longitudinal cross-sectional view (a cross-sectional view parallel to the width and thickness directions) of a conveyor belt according to an embodiment of the present invention, Fig. 2 is a perspective view showing a state in which the conveyor belt according to the embodiment is stretched over a pair of pulleys of a conveyor belt device, with a part of the conveyor belt cut away.

[0011] As shown in Figures 1 and 2, the conveyor belt 1 has a meandering prevention guide 3 attached to the center of one side (back side) of the belt base material 2 along the running direction (indicated by an arrow) of the conveyor belt 1. The meandering prevention guide 3 has a cross-sectional shape of, for example, a trapezoidal shape, and is also called a V guide. The meandering prevention guide 3 is formed by processing a porous fluororesin rod into a predetermined shape. The meandering prevention guide 3 may be directly heat-sealed to the belt base material 2, or may be adhered to the belt base material 2 via an adhesive layer. The belt base material 2 to which the meandering prevention guide 3 is attached is joined endlessly to form the conveyor belt 1.

[0012] For example, a fluororesin layer formed on the surface of a glass fiber woven fabric or an aramid fiber woven fabric is used as the belt substrate 2. For example, polytetrafluoroethylene (PTFE) or perfluoroalkoxyalkane (PFA) is used as the porous fluororesin material constituting the meandering prevention guide 3.

[0013] 2, a pair of pulleys 10 of the conveyor belt device has, for example, a V-shaped groove 10a formed in the center thereof in accordance with the shape of the meandering prevention guide 3 of the conveyor belt 1. The conveyor belt 1 is stretched over the pair of pulleys 10 with the meandering prevention guide 3 fitted in the groove 10a of the pulleys 10.

[0014] Alternatively, a groove may be provided at each end of the pulley, and a meandering prevention guide may be provided at each end of the belt base material in correspondence therewith. In this way, the number and positions of the meandering prevention guides can be appropriately changed as necessary.

[0015] In an embodiment, the porous fluororesin rod constituting the meandering prevention guide 3 has a microstructure in which nodes and fibrils are arranged alternately in the longitudinal direction in a longitudinal cross section (cross section parallel to the longitudinal and thickness directions) cut along the longitudinal direction, the number of node-fibril pairs per 200 μm straight line along the longitudinal direction is 11 or more, and the porosity is 30 to 90%. A node is an aggregate of fluororesin, and a fibril is a portion located between the nodes and connecting them. In the porous fluororesin rod, holes are formed in the gaps between the fibrils, making it porous.

[0016] In an embodiment, a porous fluororesin rod, such as a porous polytetrafluoroethylene (PTFE) rod, can be produced as follows.

[0017] An appropriate amount of extrusion aid, such as naphtha, is added to the PTFE fine powder, and then mixed using a turbular mixer to prepare a mixture. The mixture is molded into a preform of appropriate shape using a preformer. The preform is fed into an extruder to obtain a rod-shaped extrusion product, which is then dried in a heating furnace to remove the extrusion aid. The dried extrusion product is uniaxially stretched in the length direction at a temperature below the melting point of PTFE.

[0018] By uniaxially stretching the rod-shaped extrusion in the longitudinal direction, a microstructure is formed in which nodes and fibrils are arranged alternately in the longitudinal direction in a longitudinal cross section cut along the longitudinal direction, and pores are formed in the gaps between the fibrils, making it possible to produce a porous PTFE rod.

[0019] At this time, the porosity can be adjusted to 30 to 90% by appropriately setting the stretching ratio in the longitudinal direction of the PTFE rod.

[0020] Then, compressive stress is applied to the porous PTFE rod in the longitudinal direction, and the compressed state is baked at a temperature equal to or higher than the melting point of PTFE to heat fix the microstructure in which nodes and fibrils are alternately arranged in the longitudinal direction. In this way, a porous PTFE rod having a regular microstructure including nodes and fibrils can be produced.

[0021] Whether or not a porous PTFE rod is suitable for use as a meandering prevention guide for a conveyor belt can be evaluated by porosity measurement, bending test, compression test, and cross-sectional observation, as will be described in detail later. EXAMPLES

[0022] A PTFE rod to be used as a guide to prevent meandering of a conveyor belt was manufactured as follows.

[0023] Example 1 To 100 parts by mass of PTFE Fine Powder 650-J (manufactured by Mitsui-Chemours Fluoro Products), 18 parts by mass of naphtha was added as an extrusion aid, and then mixed using a turbular mixer to prepare a mixture. The mixture was then molded into a cylindrical shape using a preformer. The obtained preform was fed into an extruder to obtain a rod-shaped extrusion molded product with a nearly square cross section. The obtained extrusion molded product was dried in a heating furnace to remove the extrusion aid. The extrusion molded product was uniaxially stretched 2.5 times in the length direction below the melting point of PTFE. After stretching, heat setting was performed at a temperature above the melting point of PTFE under the condition of 10% compression in the length direction. In this way, a porous PTFE rod with a width of about 4 mm and a thickness of about 4 mm was produced.

[0024] Examples 2 to 4 A porous PTFE rod was produced in the same manner as in Example 1, except that the stretching ratio during uniaxial stretching was changed in order to adjust the porosity.

[0025] Comparative Example 1 A non-stretched PTFE rod was prepared.

[0026] Comparative Examples 2 to 3 To adjust the porosity, the PTFE rod was uniaxially stretched, and then heat-set at a temperature equal to or higher than the melting point of PTFE without compressing it in the longitudinal direction. A porous PTFE rod was produced in the same manner as in Example 1.

[0027] For each of the obtained PTFE rods, a porosity measurement, a compression test, a bending test, and cross-sectional SEM observation were carried out as described below.

[0028] <Porosity measurement> The porosity of the PTFE rod can be measured as follows. The apparent specific gravity d of the PTFE rod is measured by the underwater displacement method. The measurement of the apparent specific gravity by the underwater displacement method can be performed by the method described in JIS K 7112:1999. The specific gravity of PTFE is set to 2.2, and the porosity P (%) is calculated by the following formula. P = {(2.2-d) / 2.2} x 100.

[0029] <Bending test> The bending test will be described with reference to FIG. First, a PTFE rod 5 with a width of about 4 mm and a thickness of about 4 mm was cut to a length of 300 mm to prepare a sample. The width and thickness of the PTFE rod 5 were measured to obtain actual values. A weight 22 of 150 g was fixed to each end of the sample. Next, a SUS rod 21 with a diameter of 5 mm was placed so that its length direction was horizontal, and the sample was placed on the SUS rod 21. At this time, the length direction of the SUS rod 21 and the length direction of the sample were orthogonalized, the center of the length direction of the sample was in contact with the SUS rod 21, and both ends of the sample were hung down below the SUS rod 21. The distance from one end to the other end of the hanging sample (2R in FIG. 3) was measured, and the value obtained by dividing this distance by 2 was determined as the minimum bending R.

[0030] Although the SUS rod 21 does not have a groove 10a like the pulley 10 shown in Figure 2, the contact of the PTFE rod sample with the outer surface (cylindrical surface) of the SUS rod 21 can be considered to be equivalent to the contact of the anti-wandering rod 3 with the outer surface of the groove 10a.

[0031] For example, the PTFE rod of Example 1 has a 2R of 40 mm in FIG. 3, and therefore the minimum bending R is 20 mm.

[0032] Table 1 shows the results of the bending test of the PTFE rods of Examples 1 to 4 and Comparative Examples 1 to 3. In Comparative Example 1, when the sample was placed on the SUS rod 21, both ends did not hang down below the SUS rod 21, so the minimum bending R could not be measured, and therefore "measurable" is displayed.

[0033] [Table 1]

[0034] As can be seen from Table 1, all of the PTFE rods of Examples 1 to 4 had smaller minimum bending R compared to the PTFE rods of Comparative Examples 1 to 3.

[0035] The higher the stretchability in the length direction of the PTFE rod sample, the more likely it is that it can bend following the outer surface (cylindrical surface) of the SUS rod 21. For this reason, it is considered that the higher the stretchability in the length direction of the sample, the smaller the minimum bending R becomes, and the closer it is to 2.5 mm, which is the radius of the SUS rod 21. Therefore, the results in Table 1 show that all of the porous PTFE rods of Examples 1 to 4 have higher stretchability in the length direction than the PTFE rods of Comparative Examples 1 to 3. In this way, it is considered that the porous PTFE rods of Examples 1 to 4 contribute to the miniaturization of pulleys and conveyor belt devices.

[0036] If the porosity of the porous PTFE rod is too high, there is a concern that the strength in the thickness direction will decrease, and therefore the porosity of the porous PTFE rod is preferably 40 to 70%.

[0037] <Compression test> The samples used in the compression test and the compression test method will be described with reference to Figs. 4(a) to (d). First, a PTFE rod 5 having a width of about 4 mm, a thickness of about 4 mm, and a length of 300 mm as shown in Fig. 4(a) was cut to a length of about 4 mm to cut out a cubic sample 6 as shown in Fig. 4(b). The length, width, and thickness of the obtained sample 6 were measured to obtain actual dimensions. The obtained actual dimensions were regarded as the initial dimensions, and the length of the initial dimensions was regarded as the initial length, and the thickness of the initial dimensions was regarded as the initial thickness.

[0038] <Longitudinal compression test> A longitudinal compression test was carried out as shown in Figure 4(c). Using a compression tool with a diameter of 9 mm, the sample 6 was compressed in the length direction of the original PTFE rod 5 with a compression force that produced a compression rate of 5 mm / min. The length of the sample after compression was measured to determine the longitudinal displacement.

[0039] From the compressive force, the area of ​​the surface perpendicular to the length direction of sample 6, the initial length and the displacement in the length direction, 0.1 N / mm 2 The compression rate (%) in the longitudinal direction was calculated when the specimen was compressed under a pressure of 100 mm.

[0040] In the longitudinal compression test, the dimensional change rate in the thickness direction was also measured in the state where a compressive force of 30 N was applied in the longitudinal direction at the end of compression, as described below.

[0041] In the same manner as above, Sample 6 was compressed in the length direction until the compressive force reached 30 N, and the thickness of Sample 6 was measured in the compressed state (without releasing the compressive force) to obtain the thickness direction displacement. The thickness dimension change rate (%) after compression in the length direction under a load of 30 N was calculated from the initial thickness and the thickness direction displacement.

[0042] <Compression test in thickness direction> A thickness direction compression test was carried out as shown in Figure 4(d). Using a compression tool with a diameter of 9 mm, Sample 6 was compressed in the thickness direction with a compression force that produced a compression speed of 5 mm / min. The thickness of the sample after compression was measured to determine the displacement in the thickness direction.

[0043] From the compression force, the area of ​​the surface perpendicular to the thickness direction of sample 6, the initial thickness, and the displacement in the thickness direction, 0.1 N / mm 2 The compression rate (%) in the thickness direction was calculated when the specimen was compressed under a pressure of 100 g.

[0044] <Calculation of compression ratio> The compressibility ratio was calculated by dividing the compressibility in the length direction by the compressibility in the thickness direction. Table 2 shows the results of the compression tests of the samples of Examples 1 to 4 and Comparative Examples 1 to 3.

[0045] [Table 2]

[0046] As can be seen from Table 2, the compression ratio (length direction / thickness direction) was large for all of the samples of Examples 1 to 4. That is, it was found that the samples of Examples 1 to 4 were difficult to compress in the thickness direction due to their high strength, and were easily compressed in the length direction due to their high elasticity.

[0047] In contrast, for all the samples of Comparative Examples 1 to 3, the ratio of the compression rate (length direction / thickness direction) was around 1. That is, it was found that for the samples of Comparative Examples 1 to 3, the strength and stretchability in the thickness direction and the length direction were comparable.

[0048] Also, for all the samples of Examples 1 to 4, despite the high compression rate in the length direction, the change rate of the thickness dimension after 30 N load compression in the length direction was low. That is, it was found that for the samples of Examples 1 to 4, the stretchability in the length direction was high, and even when stretching and contracting in the length direction, the dimensions in the thickness direction were less likely to change.

[0049] <SEM Observation> The porous PTFE rods of Examples 1, 2 and Comparative Examples 2, 3 were each cut in half along the longitudinal section (a cross-section parallel to the length direction and the thickness direction) along the length direction. This cut surface was subjected to observation with a scanning electron microscope (SEM) at a magnification of 500 times.

[0050] Fig. 5 shows the SEM image of the porous PTFE rod (porosity 40%) of Example 1, Fig. 6 shows the SEM image of the porous PTFE rod (porosity 40%) of Comparative Example 2, Fig. 7 shows the SEM image of the porous PTFE rod (porosity 50%) of Example 3, and Fig. 8 shows the SEM image of the porous PTFE rod (porosity 50%) of Comparative Example 3, respectively.

[0051] In each SEM image, the left and right correspond to the length direction of the sample, and the top and bottom correspond to the thickness direction of the sample, respectively. In each SEM image, the densely visible part is the node which is an aggregate of PTFE resin, and the part located between the nodes and connecting the nodes is the fibril.

[0052] In the SEM images of Examples 1 and 2 shown in Figs. 5 and 7, the interval between the nodes (the width of the fibril) was narrow. Also, the node shape was vertically long and horizontally thin, and had a tendency to be arranged thinly and long in the vertical direction. Therefore, it is considered that the stretchability in the length direction was increased while maintaining the thickness strength.

[0053] In the SEM images of Comparative Examples 2 and 3 shown in Figures 6 and 8, the intervals between the nodes (fibril width) were wider than in the SEM images of Examples 1 and 2 shown in Figures 5 and 7. The node shapes were also irregular, and the ratio of the node width to the node length tended to be large. Such nodes were arranged randomly. This is thought to have resulted in lower elasticity in the longitudinal direction.

[0054] In order to compare the differences in the microstructures observed in the SEM images of Examples 1 and 2 and Comparative Examples 2 and 3 as described above, the following evaluation was performed. That is, a straight line was drawn along the length direction in the cross section of the rod. At this time, a region where the nodes and fibrils are regularly arranged was selected and the straight line was drawn. Then, the number of node-fibril pairs per 200 μm of straight line was counted. As a result, the number of node-fibril pairs per 200 μm of straight line was 15 in Example 1, 18 in Example 2, 10 in Comparative Example 2, and 8 in Comparative Example 3.

[0055] Therefore, as in the porous PTFE rods of Examples 1 and 2, when the number of node-fibril pairs per 200 μm along the length is 11 or more, it can be said that the rods have good flexibility in the length direction and are hard in the thickness direction, exhibiting mechanical properties suitable for the anti-wandering guide of a conveyor belt.

[0056] Although some embodiments of the present invention have been described, these embodiments are presented as examples and are not intended to limit the scope of the invention. These novel embodiments can be implemented in various other forms, and various omissions, substitutions, and modifications can be made without departing from the spirit of the invention. These embodiments and their modifications are included in the scope and spirit of the invention, and are included in the scope of the invention and its equivalents described in the claims. [Explanation of symbols]

[0057] 1...conveyor belt, 2...belt base material, 3...anti-meandering guide, 5...PTFE rod, 6...sample, 10...pulley, 10a...groove, 21...SUS rod, 22...weight.

Claims

1. A conveyor belt having a belt base material and a meandering prevention guide attached to a portion of one surface of the belt base material, the meandering prevention guide is attached along the running direction of the conveyor belt and is made of a porous fluororesin rod, the rod has a microstructure in which nodes and fibrils are arranged alternately in the longitudinal direction in a longitudinal cross section cut along the longitudinal direction, the number of node-fibril pairs per 200 μm straight line along the longitudinal direction is 11 or more, and the porosity is 30 to 90%.

2. 2. The conveyor belt of claim 1, wherein the porous fluororesin comprises polytetrafluoroethylene.

Citation Information

Patent Citations

  • Endless belt having meandering prevention guide

    JP2012014201A